Random and match game for education purposes with model learning technology system architecture. (July 2019) - Rahim, R.; Kurniasih, N; Daengs GS, A; Saddhono, K; Riasti, B K; Rangka, I B; Kurniawan, D E; Permana, Erwin Putera; Anam, Fatkul; Listiawan, Tomi; Rumambo Pandin, Moses Glorino; Gumono, G; et al.
Abstract: Education in Indonesia still faces various problems and challenges in teaching and learning process both internal and external factors such as props, media and also implementation of information technology. The use of multimedia-based learning media in the learning process will helps students to understand the material to be delivered. Random and match is a game consisting of 4 different games that are addressed to kindergarten children to know the use of technology positively in learning process, and by applying Model Learning Technology System Architecture learning an utilization using computer will be more useful for teacher and kindergarten students.